DETERMINAN SUSTAINABILITY REPORT DAN PENGARUH TERHADAP NILAI PERUSAHAAN - Rizal Restu Wicaksono; Aditya Septiani (Diponegoro Journal of Accounting, 2020)
Sustainability reporting disclosure is one of issue which large companies concern about nowadays due to increasing company awareness to create value for its operational activities. This aim of this study is to analyze the determinants of sustainability report and its effect to firm value.This study examines the sustainability practices in the sustainability report of public listed companies in Indonesia Stock Exchange, specifically non-financial corporation, for the year 2014-2017. Based on the purposive sampling method there are 20 companies which meet the sampling criteria. The GRI G4 index is used to pull out broad reports of sustainability report. The analytical method used are multiple regression analysis and sobel test for path analysisPartial hypothesis test show that firm size has negative effect on sustainability report disclosure. report. Industry type and growth opportunity has positive effect on sustainability report disclosure.However, leverage, profitability, and liquidity have no effect on sustainability report disclosure. The result of indirectly test showed that firm characteristics which are firm size, industry type, leverage, profitability, liquidity, and growth opportunity have no significant effect on firm value through financial distress as an intervening variable and sustainability report is not proven as an intervening variable.